You Can Check Out Any Time You Like, but Can You Ever Leave? A Theory of Firm Value Capture from Alumni - Fulmer, Ingrid Smithey; Call, Matthew L.; Conlon, Donald E.; Klotz, Anthony C. (Organization Science, 2024)
In modern organizations, key sources of competitive advantage are embedded in employees. Management theory has traditionally viewed employee exit as the end of firms’ relationships with employees and, consequently, the end of access to human capital and other resources embedded in departing individuals. However, recent research suggests that firms can benefit from the continuation of relationships with alumni employees. We argue that how organizations create and maintain connections to alumni is critical, as it shapes the nature of potentially valuable organization-level alumni resources. We develop a theory of firm value capture from alumni that explains how firms’ norms and policies before, during, and after employee exit affect firms’ alumni relations climate—a shared perception among a firm’s current and former employees that the firm values alumni. We further theorize that the alumni relations climate will lead to creation of firm-level alumni resources, with the configuration of these resources shaped by alumni identification. That is, the extent to which firms’ alumni identify with the firm versus with members of the firm’s remaining workforce (or balanced between the two) will have implications for the configuration of alumni resources that are potentially accessible to the firm. Our theory describes how these different alumni resource configurations come with inherent benefits and costs when it comes to the value that firms are able to capture from their alumni resources. We illustrate the value of this theoretical perspective by identifying meaningful practical implications and avenues for future research.